Nutritional potential of Vasconcellea quercifolia A. St.-Hil. green fruit flour - Lilian de Fátima Ferreira da Silva; Kétlin Fernanda Rodrigues; Eduardo Miranda Ethur; Lucélia Hoehne; Claucia Fernanda Volken de Souza; Daisa Hakbart Bonemann; Anderson Schwingel Ribeiro; Elisete Maria de Freitas (Brazilian Journal of Food Technology, 2022)
Abstract Non-conventional food plants have a variety of bioactive compounds with nutritional value. Vasconcellea quercifolia A. St.-Hil., belonging to the Caricaceae family, is a dietary alternative with excellent nutritional composition. This study aimed at characterizing the nutritional composition of mountain papaya (V. quercifolia) green fruit flour, in order to incorporate it in a functional food. For that purpose, the flour was characterized regarding its macro and micronutrients, anti-nutritional factors, pH, water activity, and color. This flour showed contents of carbohydrate of 22.31%; protein of 9.65%; dietary fiber of 32.80%; lipids of 14.95%, 63.56% of which are unsaturated fatty acids, especially oleic acid; and ash of 9.10%, with higher concentrations for potassium, calcium and magnesium. Therefore, V. quercifolia flour had good nutritional characteristics and might be used as supplementary food.